Decisions about the use of psychotropic medication during pregnancy: a qualitative study - Irene Petersen; Vanessa Pinfold; Sarah Hamilton; Fiona Stevenson; Charlotte Walker; Ceri R J Dare; Harminder Kaur; Ruth Lambley; Paulina Szymczynska; Vicky Nicolls (BMJ Open)
Objective To understand the perspectives of women with severe mental illness concerning the use of psychotropic medicines while pregnant.Design Interviews conducted by female peer researchers with personal experience of making or considering decisions about using psychotropic medicines in pregnancy, supported by professional researchers.Participants 12 women who had had a baby in the past 5 years and had taken antipsychotics or mood-stabilisers for severe mental illness within the 12-month period immediately prior to that pregnancy. Recruitment to the study was via peer networks and the women interviewed came from different regions of England.Setting Interviews were arranged in places where women felt comfortable and that accommodated their childcare needs including their home, local library and the research office.Results The views expressed demonstrated complex attempts to engage with decision-making about the use of psychotropic medicines in pregnancy. In nearly all cases, the women expressed the view that healthcare professionals had access to limited information leaving women to rely on experiential and common sense evidence when making decisions about medicine taking during pregnancy.Conclusions The findings complement existing work using electronic health records by providing explanations for the discontinuation of psychotropic medicines in pregnancy. Further work is necessary to understand health professionals’ perspectives on the provision of services and care to women with severe mental illness during pregnancy.